Pendekatan Normatif sebagai Metodologi Penelitian Hukum Islam - Parid Sidik (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Islam as a complete religion cannot be separated from some of the rules in it, or better known as Shari'a. With this Shari'a, a law appears that regulates the pattern of human life. Responding to problems in society must be based on a dynamic approach and each of them is capable and there is no reason to abandon these problems and practice through a normative approach.The emergence of a normative approach is the result of the thoughts of Muslim scholars and scholars to develop scientific treasures in responding to legal issues that are in the midst of society. Because the world is growing rapidly with various problems and causing problems in social life. Then comes a normative approach to be used as a basis in answering questions of Islamic law This research is descriptive in nature, namely research that presents various literature and then is developed and analyzed and then draws conclusions. The results of this study are that the normative approach in research contributes in the form of: a). examines Islamic law in a structured manner, b). has a strong foundation c). Normative approaches in scientific disciplines are part of Normative-thelogic and integration-interconnections in their studies. Keywords: Normative, Islamic Law, Integration-Interconnection.